Health capital and economic growth in Cameroon - Marcel, Gouenet (EuroEconomica, 2023)
From the macroeconomic statistics of the WHO, datum EDS and the World Bank data base, effects of the health on the growth in Cameroon are estimated thanks to a model of the production function. The macroeconomic estimations allowed to establish that the evolution of the variables of the human resources was not favourable to the increase of the GDP(Gross Domestic Product), in particular the contribution of the hand of work and the variable of the healthy living that is the life expectancy.